Litchi aspartic protease LcAP1 enhances plant resistance via suppressing cell death triggered by the pectate lyase PlPeL8 from Peronophythora litchii - Li, Wen (The New phytologist, 2024)
© 2024 The Authors New Phytologist © 2024 New Phytologist Foundation.